Efek Moderasi Pemahaman Pajak pada Hubungan Antara Theory of Planned Behavior Terhadap Kepatuhan Wajib Pajak - Talithahandari, Aisyah; Askandar, Noor Shodiq; Mahsuni, Abdul Wahid (Universitas Islam Malang, 2024)
In this research, the level of taxpayer compliance is influenced by several factors explained in the Theory of Planned Behavior, including attitudes, subjective norms, and percieved behavioral control. Tax understanding was also tested as a moderating variable that has the potential to influence the relationship between these factors. Furthermore, it is known that in the 2022 tax year, there was a decrease in tax reporting carried out by taxpayers, both corporate and individual, throughout Indonesia. This research applying the Structural Equation Model (SEM) model implemented via SmartPLS 3.2.9 to carry out the analysis. As a result, there is a significant and positive correlation between Attitudes towards Taxpayer Compliance and also between Subjective Norms and Taxpayer Compliance. Data collection in this research was carried out using a questionnaire. In this analysis, it is proven that there is a significant and positive relationship between Behavioral Control and Taxpayer Compliance. It has been proven that tax understanding moderately and significantly influences the relationship between attitudes and taxpayer compliance. A similar relationship between Subjective Norms and Behavioral Control and Taxpayer Compliance, which is identified simultaneously, is also influenced by tax understanding. These findings reveal that tax understanding positively moderates the relationship between these factors and Taxpayer Compliance.Keywords: Theory of planned behavior, attitudes, subjective norms, percieved behavioral control, tax compliance, tax understanding.